Optimization of parameters for micro hot embossing of aluminum alloy with a silicon die - Guo, Haiqing (2014)
In the traditional micro hot embossing process, brittle silicon molds are particularly vulnerable to failure during demolding because of adhesion and thermal stress. Experiments have been developed to analyze the feasibility of using alternative mold materials. In this investigation, DOE (design of experiment) method is employed to analyze the hot embossing of aluminum alloy with a silicon die so as to produce aluminum alloy mold for the hot embossing of polymeric substrates. From the chosen experimental factors, embossing temperature has been determined to have a significant influence on the width replication accuracy, followed by the embossing force. Molding rate has the least influence on the replication accuracy. An empirical formula is developed from the experimental results to obtain the optimum experimental conditions within a chosen range. In addition, no obvious relationship has been observed between the surface roughness and chosen experimental factors.